Pengaruh Infrastruktur dan Keterkaitan Spasial Terhadap Konvergensi Beta di Indonesia - Anisa Fahmi (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2015)
Motivated inter-regional disparities condition that occurs persistently, this thesis examines the Indonesian economy in the long run, whether it will tend to converge or diverge. This convergence is based on the Solow Neoclassical growth theory which assumes the existence of diminishing returns to capital so that when the developed countries reach steady state conditions, developing countries will continuous growth up to ‘catch-up‘ with developed countries. This thesis also focuses on the influence of spatial dependency and infrastructure since regional economics perspective, each region can not be treated as a stand-alone unit. Economical and political situation of a region will influence policy in that region which will also have an impact to the neighboring regions. The estimation results of spatial cross-regressive model using fixed effect method consistently confirmed that the Indonesian economy in the long term will likely converge with a speed of 8.08 percent per year. Other finding is, road infrastructure has a positive effect on economic growth and investment and road infrastructure are spatially showed a positive effect on economic growth. In other words, the investment and the infrastructure of a region not only affect the economic growth of that region but also to the economy of the contiguous region.